A modified hot thermocouple apparatus for the study of molten oxide solidification and crystallization. (2nd February 2016) - Esfahani, Shaghayegh; Danaei, Karim; Budurea, Daniel; Barati, Mansoor
Abstract: The hot thermocouple technique (HTT) is an experimental method primarily used for studying high temperature phase transformations and interactions. The thermocouple driver is the main component of the apparatus, allowing heating and temperature measurement of the thermocouple that acts as a heating element and temperature sensor simultaneously. Previous setups have employed an ac (alternating current) power feed to the thermocouple, creating inherent limitations to the time interval and frequency of temperature sensing and control. In this article, the development of a dc (direct current)-based thermocouple driver is discussed. The new setup allows higher frequency (480 Hz) of heating pulses applied to the thermocouple. The higher switching frequency improves the thermocouple temperature reading accuracy and decreases the time interval between the measurements by a factor of eight, compared to existing HTT devices. The development of a dc power HTT apparatus, its calibration, and examples of its use in the studies of the crystallization of oxide mixtures are presented in this article.